Digital Transformation in the Management of the National Archives of the Republic of Indonesia: A Qualitative Analysis of Challenges and Opportunities in Improving the Efficiency and Effectiveness of Archive Management - syahidan, amir (Social Impact Journal, 2024)
This study examines the digital transformation of national archives management in Indonesia, using qualitative analysis to identify challenges and opportunities for improving efficiency and effectiveness. The research reveals that high costs of digital technology implementation and limited human resources are major obstacles. However, digital transformation offers significant potential to enhance archival management efficiency through technologies like big data and artificial intelligence. The government has established policies to create a more orderly and usage-oriented archival management system. Digitalization enables electronic government administration, resulting in a more accessible, efficient, and integrated system. The transformation process involves converting files into textual documents and then into digital formats to streamline archival systems. While acknowledging potential negative impacts such as high costs and human resource limitations, the study concludes that successful digital transformation in archiving can significantly benefit Indonesia's governance. Effective digital archive management plays a crucial role in achieving better bureaucratic reform and enhancing public service delivery.